Evaluation of novel coagulation and platelet function assays in patients with chronic kidney disease. (3rd February 2022) - Abdelmaguid, Alyaa; Roberts, Lara N.; Tugores, Laura; Joslin, Jennifer R.; Hunt, Beverley J.; Parmar, Kiran; Nebres, Danilo; Naga, Salah S.; Khalil, Eman S.; Bramham, Kate
Abstract: Background: Hemostasis evaluation in chronic kidney disease (CKD) is critical for optimal management of thrombotic and bleeding events. Standard coagulation screens are inadequate for predicting coagulopathy in CKD. Objective: To evaluate hemostasis parameters in patients with different stages of CKD using novel coagulation assays. Patients/Methods: Cross‐sectional study of 30 healthy controls (HC) and 120 CKD patients (10 Stage 2, 20 Stage 3, 20 Stage 4, 20 Stage 5 not requiring renal replacement therapy, 20 transplant, 10 newly started on hemodialysis [HD], 20 established on HD). Standard laboratory tests were performed in addition to rotational thromboelastometry (ROTEM), multiple electrode aggregometry (MEA), thrombin generation assays, D‐dimer, and markers of thrombogenesis (thrombin‐antithrombin [TAT]), fibrinolysis, and endothelial activation (intercellular adhesion molecule‐1 [ICAM‐1]). Results: D‐dimer, TAT, and ICAM‐1 concentrations were significantly higher in patients with CKD than HC ( P < .01). ROTEM maximum clot firmness was significantly higher in patients than in HC ( P < .01). In CKD Stage 5 patients (pre‐HD and started HD) adenosine diphosphate and thrombin receptor activating peptide MEA tests were significantly lower than HC indicating platelet aggregation defect ( P < .05). Multivariate analysis confirmed the direct effect of estimated glomerular filtration rate (eGFR) in the variance of ROTEM and MEA tests. Endogenous thrombin potential and peak thrombin were not statistically different between groups, but Stage 5 CKD patients had prolonged lag time (7.91 vs. 6.33, P < .001) and time to thrombin peak (10.8 vs. 9.5, P < .05) compared to HC. Conclusions: Patients with CKD exhibit features of concomitant hypercoagulability measured by ROTEM and platelet dysfunction measured with MEA. eGFR was an independent determinant of platelet dysfunction and hypercoagulability.